2018
DOI: 10.4172/2155-9864.1000398
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Sickle Cell Disease (SCD) in Awka South East Nigeria

Abstract: Background: Sickle cell Diseases (SCD) is a genetic disorder. It is the most common genetic disorder affecting black race worldwide. It carries a high mortality and morbidity when not promptly and properly managed. Early detection is key to improving the quality of life of people living with sickle cell disease especially in childhood. It has resulted in reduction in mortality rate of SCD to <1% in developed countries through newborn screening but this reduction is yet to be achieved in developing countries. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A similar study in Abuja, Nigeria reported a prevalence of 1�4% for HbSS, 20�5% for HbAS and HbAA 77% [21]. Another similar study in Awka South-East Nigeria reported a prevalence of 0.3% for HbSS and 75% for HbAA genotype amongst newborns [36]. A study in Benin, Southern Nigeria found 75.3% HbAA, 20.6% HbAS, 1.1% HbAC, 2.8% HbSS, and 0.2% HbSC [12].…”
Section: Plos Onementioning
confidence: 86%
“…A similar study in Abuja, Nigeria reported a prevalence of 1�4% for HbSS, 20�5% for HbAS and HbAA 77% [21]. Another similar study in Awka South-East Nigeria reported a prevalence of 0.3% for HbSS and 75% for HbAA genotype amongst newborns [36]. A study in Benin, Southern Nigeria found 75.3% HbAA, 20.6% HbAS, 1.1% HbAC, 2.8% HbSS, and 0.2% HbSC [12].…”
Section: Plos Onementioning
confidence: 86%
“…A number of recent reports have addressed acceptability and feasibility of NBS for SCD in different areas of the country: validation of the use of IEF as a screening tool in Awka, Southeast Nigeria [1541]; affirmation of the feasibility and acceptability of a SCD screening intervention program in Lagos State using the HemoTypeSC TM POC for ease and reduced cost [1542]; evaluation of HPLC as a suitable NBS method for HGB at the National Hospital Abuja [1543]; documentation of the feasibility and acceptability of integrating HGB screening into an existing community-based maternalchild HIV program to increase awareness and demand for NBS from pregnant women in Benue State, Nigeria [1544]; acceptance of NBS based on awareness, education and cultural beliefs with a preference for screening away from the birthing site in Ibadan, Nigeria [1545]; and improvement of NBS program over time in Kaduna State, Nigeria [1546]. The use of POC testing has resulted in studies, including the report from Lagos State mentioned above on HemoTypeSC TM [1542], on their reliability and effectiveness in improving the speed of analysis and impact on acceptability on parents.…”
mentioning
confidence: 99%